Analisis Konsep Al-‘Ardh Dalam Surah At Taha Ayat 134 dan Takhsis Dalam Surah At Taubah Ayat 13 - Ramadhanti, Mutya; Harahap, Siti Mardeana (Enlightenment Publishing, 2024)
This research aims to analyze the use of the word al-ardh in Surah Taha verse 134 and the concept of takhsis in Surah At-Taubah verse 13. The use of the term al-ardh in the Qur'an has variations in meaning depending on the context of the verse, which in Surah Taha verse 134 can be interpreted as a concept of land or earth which was a sign of God's power for the previous people. This research explores the relationship between the use of the word al-ardh and God's intention of justice in providing evidence to humanity before passing judgment. On the other hand, analysis of the concept of takhsis in Surah At-Taubah verse 13 explains the Al-Qur'an's method of making legal specializations that function as restrictions or exceptions, especially in the context of the order to wage jihad against polytheists who violate the agreement. This research uses thematic interpretation methods and linguistic analysis to clarify the meaning of words in the context of the verse. The results of the analysis show that the use of the word alardh strengthens the moral message in conveying Divine justice, while the concept of takhsis in Surah At-Taubah verse 13 functions as a legal basis for the selective implementation of jihad. This research is expected to provide a deeper understanding of the linguistic and theological meaning of the verses of the Qur'an related to al-ardh and takhsis in the context of the study of Qur'anic interpretation.